Presence of Moroccan Banks in Africa: Assessment and prospects for strengthening - (:unkn) unknown (My University, 2023)
The internal performance of the Moroccan banking sector has been decisive in allowing some leading banking groups to diversify their activities internationally, particularly in Africa, through acquisitions or equity investments in local banks.The purpose of this paper, by its nature which qualifies it rather as a review article, is to conduct an analysis, on the one hand, on the nature of the relationship between subsidiaries and parent banks, by trying to shed the light, particularly, on the weight of subsidiaries in the balance sheets and results of parent banks. On the other hand, to evaluate the contribution of Moroccan banks to the financing of the economies of the host countries, and this through the analysis of the structure of the deposits and the credits realized by the subsidiaries of Moroccan banks in the countries where they are established. The main conclusions of this work are: - a strong concentration in West Africa, Central Africa and North-East Africa, - a coefficient of employment of bank deposits is below the threshold of 70%, - a low rate of banking in most host countries due to the instability of employment and income.Keywords : Subsidiaries – Africa – Banking –- Contribution-
Keywords: African Research